Identifying the level of customer satisfaction and loyalty towards Habib ( A study at Habib Ampang Point showroom 2003/2004) / Hairul Fadzlee Hisham Hasan - Hasan, Hairul Fadzlee Hisham (Faculty of Business and Management, 2005)
HABIB is today a major retailer and distributor of products ranging from finely crafted diamonds and gold bullion jewellery watches to creative gold jewellery reflecting Malaysia's rich cultural heritage. It has been an evolution fired by an aspiration to offer Malaysians the finest jewellery at competitive prices. Half a century later, this same aspiration still underlines the HABIB tradition of skill for manufacturing and retailing uniquely designed, finely crafted and avant-garde style jewellery. HABIB created stunning jewellery that embodied traditional artistry and avant-garde thinking, continuity and invention. Today, jewellery manufacturing has emerged as HABIB's primary forte, contributing to its growing reputation as a trailblazer in the gem trade.